Are men dominant? Evidence of differences between physical activity and quality of life among older adults in China - Chen, Mo; Chen, Shanping; Wu, Yuyan; Song, Di; Xie, Lijun; Shang, Yao; Chen, Zhiyi (Frontiers in Public Health, 2023)
At present, population aging is one of China's basic national conditions, and physical exercise has endless potential to cope with the aging of the population. But in modern Chinese real life, the life expectancy of men is generally lower than that of women in China, and the health status of older men is more worrying. So could it be because of the difference in physical exercise that causes the difference in the length of life of older men and older women? This paper analyzes the exercise of older men and its influence on the quality of life of older men and older women. 200 older people over 60 years old were investigated by using the SF-36 and Exercise Questionnaire. The results:(1) The scores of seven dimensions of life quality of older men were significantly lower than those of older women (P<0.001), but there was no significant difference only in physiological function (P>0.05). (2) The exercise frequency and exercise persistence of older men were significantly lower than those of older women (P<0.001), but there was no significant difference in exercise time (P>0.05). (3) All eight indexes of life quality of older men are positively correlated with four indexes of exercise (0.250